REKONSTRUKSI PEMAHAMAN HADIS: (Analisis terhadap Cakupan Hadis dalam Fatwa MUI tentang Kesetaraan Gender) - Mohammad Nawir (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
The study concluded that the hadiths about gender equality in the fatwas of the Indonesian Ulama Council (MUI) was based on the validity of the arguments hadith, such as the rules of a tradition validity , which has been tested and recognized by the Hadith scholar of classical and authoritative. This study agrees with Ibnuddin (2011) which states that the MUI in the case of interfaith marriage less open to the socio cultural and socio real political currently there in the country, resulting in a controversial fatwa. M. Quraish Shihab (2003), Yusuf al-Qaradawi (2011), which explains that to understand the traditions of the creation of women, needs to be understood metaphorically. This study differs from Asrorun Ni'am Salah M. (2012) which states that the MUI fatwa on female circumcision is neutral between the two groups. The first group stated to perform the practice of circumcision in excess and the second group who forced himself to prohibition against female circumcision absolutely. Yunahar Ilyas (1997) study which states that the hadith about the creation of woman from the rib is a sound hadith that already valid either in text or contextmeaning. This study uses the Socio-historical approach. The primary data is a collection of MUI fatwa on gender equality issues, among them the fatwa of the imam pray for women, female circumcision, interfaith marriage, female leader. While secondary sources are books of hadith, hadith and sirah Sharh al-Nabawiyah especially that rested in the MUI issued fatwa